Un improbabile precursore di Gutenberg? (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
The reconsideration of the small silver foil epigraph of the so called “Tesoro di Marengo” clarly demonstrates that the inscription has been made not “per mezzo di punzoni e stampi”, as proposed by the first publisher and never more discussed, but using a deep-drawing technique applied to the upper side, which the succeeding phases of deepening, rethink, corrections to many imperfections can be followed of.
Keywords: Latin Epigraphy; metal inscriptions; technique of execution